Poikiloderma with neutropenia: a case report - Jebran Chekr; Jan Andraws; Jubran Elias; Diana Alasmar (Journal of Medical Case Reports)
Abstract Background Poikiloderma with neutropenia is a rare genetic disorder primarily characterized by the presence of poikiloderma and congenital chronic neutropenia. Mutations in the C16orf57 gene, which encodes the USB1 protein, are implicated as the underlying cause of poikiloderma with neutropenia. Case presentation Our patient, an 11-year-old Syrian male child who presented with poikiloderma, palmoplantar keratoderma, pachyonychia, recurrent infections, and neutropenia, is considered to be the first documented case in Syria. Clinical examinations, laboratory tests, radiographic imaging, and genetic analyses have been conducted, with the latter being essential and definitive for diagnosis. Conclusion This study aimed to evaluate whether poikiloderma with neutropenia should be considered for differential diagnosis because of its diagnostic complexity, emphasizing the importance of follow-up for the early identification of potential complications.